Effect of swearing on physical performance: a mini-review - Washmuth, Nicholas B.; Stephens, Richard; Ballmann, Christopher G. (Frontiers in Psychology, 2024)
Swearing, or using taboo language with the potential to offend, has been shown to improve physical performance during short and intense tasks requiring strength and power development. While consistent ergogenic effects of swearing have been observed across studies, the mechanisms by which swearing impacts physical performance are not fully clear. Swearing has been shown to modulate physiological (i.e., heart rate, blood pressure, skin conductance), psychological (i.e., state disinhibition), and nociceptive (i.e., pain threshold, pain tolerance, pain perception) responses, thus making it plausible that these mechanisms allow swearing to positively impact physical performance. A variety of dosages of swearing (i.e., word used, intensity, frequency, quantity) have been reported to improve physical performance. Although habituation to the positive physical performance effects of swearing has not been explored formally through empirical research, habituation to swearing has been observed in other contexts. From a practical application standpoint, swearing represents a low-risk, effective, and inexpensive intervention that has the potential to acutely improve physical performance although the taboo nature of swearing may limit its utility in real-world situations. The purpose of the following review is to provide an overview of available evidence on swearing and physical performance and discuss likely underlying mechanisms. Exploration of different swearing approaches and habituation will also be highlighted and suggestions for future research will be discussed, to more comprehensively understand if swearing can be strategically used for performance enhancement.